Design and Synthesis of Minimalist Terminal Alkyne‐Containing Diazirine Photo‐Crosslinkers and Their Incorporation into Kinase Inhibitors for Cell‐ and Tissue‐Based Proteome Profiling1. Issue 33 (10th June 2013) - Li, Zhengqiu; Hao, Piliang; Li, Lin; Tan, Chelsea Y. J.; Cheng, Xiamin; Chen, Grace Y. J.; Sze, Siu Kwan; Shen, Han‐Ming; Yao, Shao Q.
<x xml:space="preserve">Abstract</x> Less is more: A minimalist "clickable" photo‐crosslinker (see scheme) was incorporated with numerous small‐molecule kinase inhibitors. The resulting probes were used for both in vitro (cell lysates) and in situ (live cells) proteome profiling, for large‐scale identification of their potential cellular kinase targets and shows improved outcomes over previous probes.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>